Optimizing antiviral agents for hepatitis B management in malignant lymphomas - Ozoya, Oluwatobi O. (Ann Transl Med, 2017)
The global scale of hepatitis B infection is well known but its impact is still being understood. Missed hepatitis B infection impacts lymphoma therapy especially increased risk of hepatitis B virus (HBV) reactivation and poor treatment outcomes. The presence of undiagnosed chronic hepatitis also undermines chronic HBV screening methods that are based on a positive HBsAg alone. The goal of this review is to evaluate the literature for optimizing antiviral therapy for lymphoma patients with HBV infection or at risk of HBV reactivation. Relevant articles for this review were identified by searching PubMed, Embase, Ovid Medline, and Scopus using the following terms, alone and in combination: “chronic hepatitis B”, “occult hepatitis B”, ”special groups”, “malignant lymphoma”, “non-Hodgkin’s lymphoma”, “Hodgkin’s lymphoma”, “immunocompromised host”, “immunosuppressive agents”, “antiviral”, “HBV reactivation”. The period of the search was restricted to a 15-year period to limit the search to optimizing antiviral agents for HBV infection in malignant lymphomas [2001–2016]. Several clinical practice guidelines recommend nucleos(t)ide analogues-entecavir, tenofovir and lamivudine among others. These agents are best initiated along with or prior to immunosuppressive therapy. Additional methods recommended for optimizing antiviral therapy include laboratory modalities such as HBV genotyping, timed measurements of HBsAg and HBV DNA levels to measure and predict antiviral treatment response. In conclusion, optimizing antiviral agents for these patients require consideration of geographic prevalence of HBV, cost of antiviral therapy or testing, screening modality, hepatitis experts, type of immunosuppressive therapy and planned duration of therapy.